Naloxegol to Treat Constipation in a Patient Taking Opioids for Cancer Pain: A Case Report. Issue 1 (1st July 2018) - Gálvez, Rafael; Maire, Coralie; Tovar, Isabel; Vargas, Pilar
Abstract : Opioid-induced constipation (OIC) is a common gastrointestinal adverse effect of opioids, which can severely affect compliance and adherence to pain medication regimens and quality of life. Naloxegol has demonstrated efficacy against OIC in several studies involving patients with nonmalignant chronic pain. Here we report efficacy and tolerability of naloxegol in a 68-year-old patient with metastatic lung cancer and severe pain, treated with opioids, who presented with OIC resistant to traditional measures. Addition of naloxegol produced rapid improvement in his OIC symptoms and no apparent adverse effects while taking extended-release morphine 130 mg orally every 12 hours.